Procedural success of transcatheter annuloplasty in ventricular and atrial functional tricuspid regurgitation - Barbieri, Fabian; Mattig, Isabel; Beyhoff, Niklas; Thevathasan, Tharusan; Romero Dorta, Elena; Skurk, Carsten; Stangl, Karl; Landmesser, Ulf; Kasner, Mario; Dreger, Henryk; Reinthaler, Markus (Frontiers in Cardiovascular Medicine, 2023)
Background: Transcatheter annuloplasty is meant to target annular dilatation and is therefore mainly applied in functional tricuspid regurgitation (TR). Due to recent recognition of varying disease pathophysiology and differentiation of ventricular and atrial functional TR (VFTR and AFTR), comparative data regarding procedural success for both disease entities are required. Methods: In this consecutively enrolled observational cohort study, 65 patients undergoing transcatheter annuloplasty with the Cardioband® device were divided into VFTR (n=35, 53.8%) and AFTR (n=30, 46.2%). Procedural success was assessed by comparing changes in annulus dilatation, vena contracta (VC) width, effective regurgitation orifice area (EROA) as well as reduction in TR severity. Results: Overall, improvement of TR by at least two grades was achieved in 59 patients (90.8%), improvement by at least three grades in 32 patients (49.2%). Residual TR ≤2 was observed in 52 (80.0%) of patients. There were no significant differences in annulus diameter reduction [VFTR: 11mm (9-13) versus AFTR: 12mm (9-16), p=0.210], VC reduction [12mm (8-14) versus 12mm (7-14), p=0.868] and EROA reduction [0.62cm² (0.45-1.10) versus 0.54cm² (0.40-0.70), p=0.204]. Improvement by at least two grades [27 (90.0%) versus 32 (91.4%), p=1.0] and three grades [14 (46.7%) versus 18 (51.4%), p=0.805] were similar in VFTR and AFTR. There was no significant difference in the accomplishment of TR grade ≤2 [21 (70.0%) versus 31 (88.6%), p=0.118]. Conclusion: Transcatheter annuloplasty with the Cardioband® may be applied in both, VFTR and AFTR with evidence of significant procedural TR reduction according to our results from a real-world scenario.